ISOLATION AND IDETIFICATION OF LACTIC ACID BACTERIA FROM ANNA APPLE CULTIVAR (Malus domestica var. Anna) AS POTENTIAL EXOPOLYSACCHARIDE PRODUCER - Kusmiyati, Nur; Zubaidah, Elok; Lesmana, Emmanuel Raphael; Utami, Ulfah (Food and Feed Research, 2026)
Lactic acid bacteria (LABs) are a group of microorganisms frequently found in various fermented foods, fruits, vegetables, and the human gut microflora. LABs are known for its ability to produce lactic acid via carbohydrate fermentation (typically simple sugars), which play major roles as flavour compounds as well as in maintaining food safety and stability. Furthermore, LABs are classified as food grade microorganisms since they are safe for human consumption, non-pathogenic, and generally does not produce compounds which are toxic to humans. Several species of LABs are a known to produce exopolysaccharide (EPS), a polysaccharide which is excreted from the cell during bacterial growth phase. LAB-produced EPS have comparable physicochemical properties to certain plant polysaccharides such as guar gum or pectin. Hence, it is commonly used in food industries as a thickener, stabilizer, and to improve rheological properties of food products. In the baking industry (especially bread making), EPS plays an important role as a partial replacement for gluten, improving bread volume, and reduce bread crumbliness, resulting in better product quality. This study aims to isolate and identify LABs from the mesocarp (fruit flesh) of Anna apple cultivar (Malus domestica var. Anna), as a potential EPS producer. Isolation and purification of LAB produced eight isolates, respectively BAA-1 through BAA-8. The isolates were then characterized via Gram staining, endospore staining, catalase activity assay, carbohydrate fermentation assay, and EPS production yield. Results indicate that isolate BAA-5 and BAA-8 produced the highest yields of EPS, which were 3350 mg/L and 3050 mg/L respectively. Further molecular identification showed that isolate BAA-5 had a 98.68% gene similarity to Lacticaseibacillus paracasei, while isolate BAA-8 had a 99.74% similarity to Lactiplantibacillus plantarum. Thus, the two isolates can potentially be developed as functional agents in food industrial applications.